(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Seasonal abundance of the sucking insect pests particularly the aphid and jassid on the cotton Gossypium hirsutum varieties CB12, CB13, CB14, CB15 and HC1, which are being cultivated in different Cotton Research and Multiplication Farms of Bangladesh, were studied from July 2018 to January 2019 at Gazipur in Bangladesh. The study also investigated the impact of weather parameters on the incidence of the pests. Aphids showed their abundance from the second week of October to the third week of November and the population revealed fluctuation. Aphid population reached to the peak in the fourth week of October (31.2/leaf) on HC1 followed by CB14, CB12, CB15 and CB13 cotton varieties. The weather factors collectively predicted 79.5% to 84.6% contribution on the abundance of aphid, and the highest and lowest effects were found on the varieties HC1 and CB14, respectively. Jassids showed their abundance from the first week of November to the second week of January and reached to the peak (7.2 leaf-1) in the fourth week of November on CB15 followed by CB12, CB13, HC1 and CB14 cotton varieties. The combination effect of the weather factors ranged from 57.4% to 71.0% abundances of jassid and the highest and lowest results were found on HC1 and CB15 varieties, respectively. J Bangladesh Agril Univ 19(1): 8–13, 2021 https://doi.org/10.5455/JBAU.24989